Evaluation of the potential of ultrasound-mediated drug delivery for the treatment of ovarian cancer through preclinical studies - Wang, Yi-Chao; Tian, Jing-Yan; Han, Ying-Ying; Liu, Yun-Fei; Chen, Si-Yao; Guo, Feng-Jun (Frontiers in Oncology, 2022)
Ovarian cancer (OC) has the greatest mortality rate among gynecological cancers, with a five-year survival rate of <50%. Contemporary adjuvant chemotherapy mostly fails in the case of OCs that are refractory, metastatic, recurrent, and drug-resistant. Emerging ultrasound (US)-mediated technologies show remarkable promise in overcoming these challenges. Absorption of US waves by the tissue results in the generation of heat due to its thermal effect causing increased diffusion of drugs from the carriers and triggering sonoporation by increasing the permeability of the cancer cells. Certain frequencies of US waves could also produce a cavitation effect on drug-filled microbubbles (MBs, phospholipid bilayers) thereby generating shear force and acoustic streaming that could assist drug release from the MBs, and promote the permeability of the cell membrane. A new class of nanoparticles that carry therapeutic agents and are guided by US contrast agents for precision delivery to the site of the ovarian tumor has been developed. Phase-shifting of nanoparticles by US sonication has also been engineered to enhance the drug delivery to the ovarian tumor site. These technologies have been used for targeting the ovarian cancer stem cells and protein moieties that are particularly elevated in OCs including luteinizing hormone-releasing hormone, folic acid receptor, and vascular endothelial growth factor. When compared to healthy ovarian tissue, the homeostatic parameters at the tissue microenvironment including pH, oxygen levels, and glucose metabolism differ significantly in ovarian tumors. US-based technologies have been developed to take advantage of these tumor-specific alterations for precision drug delivery. Preclinical efficacy of US-based targeting of currently used clinical chemotherapies presented in this review has the potential for rapid human translation, especially for formulations that use all substances that are deemed to be generally safe by the U.S. Food and Drug Administration.